(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Piractwo morskie posiada bardzo długą historię i przez pewien czas zostało już uznane za zbrodnię przeszłości. Ponowne narodzenie się tego zjawiska zagroziło handlowi międzynarodowemu, bezpieczeństwu międzynarodowemu, przez co stało się pewnego rodzaju fenomenem współczesnego świata. Przyczyn rozwoju współczesnego piractwa morskiego można szukać w ubóstwie państw przybrzeżnych, chęci zysku, słabości państw i ich funkcji policyjnych, nawet, jak w przypadku Somalii, braku skutecznego rządu i załamania ekonomicznego, jak również w braku skutecznych mechanizmów prawnych oraz skutecznych działań zmierzających do walki ze zjawiskiem piractwa morskiego. Niniejsze opracowanie stanowi próbę uporządkowania definicji szeroko rozumianego piractwa morskiego oraz opisuje główne nurty działań, podejmowanych przez społeczność międzynarodową, mających na celu walkę z tym zjawiskiem. The piracy possesses very long history and for some time has been recognized as a crime of the past. The renewed of its occurrence threatened to the international commerce, to the international safety, where through has become a phenomenon of the present world. Reasons of the development of the present piracy one can seek in the poverty coastal states, greed, weakness of some states and lack of their police-functions Even, as the case of Somalia shows, the lack of the efficient government and the economic break down, as well as lack of the efficient legal mechanisms and efficient activities pursuing of the fight with the occurrence of the piracy. Illegal activities at sea can be divided in two groups: piratical activities and armed robbery at sea and acts of terrorism of sea. International law has not one unified definition of the piracy. General frames helpful in defining are established in the United Nations Convention on the Law of the Sea (UNCLOS) which however by instituting conditions „for private ends” and „on the high seas”, considerably restricts its use. Illegal acts of violence with relation to the ship, outside the high sea are defined by the International Maritime Organization, as armed robbery at sea to which the universal jurisdiction, instituted in the UNCLOS convention, is not in force. The key element that allows differentiating the piracy and the terrorism at sea is the motive. Pirates make it for the profit, and sea-terrorists are to gain, so called, the effect of the theatre. In the context of increasing numbers of piratical attacks, especially at the coast of Somalia, Security Council of the United Nations and states undertook more intense activities. It should be however noted that states directly subject are rather reluctant to accusing and the sentencing of pirates in national courts in consideration of the complicated legal character of such matters and the necessity of assuring of the suitable standards of human rights. The question stays whether in the international law is necessary the introduction of the equal mechanism of accusing, the sentencing and punishing of captive pirates. In spite of the undertaken activities, accused pirates often go free because of the lack of proper legal bases or the political will for sentencing and the condemnation. The present elaboration tries to systematize the definition of the widely understood piracy and describes mainstreams of activities undertaken by the international community, targeting the fight with this problem.